Abdominal compartment syndrome and intra-abdominal hypertension. Issue 6 (December 2019) - Pereira, Bruno M.
Abstract : Purpose of review: Abdominal compartment syndrome (ACS) is a severe complication resulting from an acute and sustained increase in intra-abdominal pressure (IAP), causing significant morbidity and mortality. Although prospective double-blinded, randomized trials, and evidence-based analysis are lacking there is new evidence that still demonstrates high morbidity and mortality in critically ill populations because of intra-abdominal hypertension (IAH) in the 21st century. The objective of this review is to alert the health professional about this important diagnosis and to highlight the latest updates proposed by the World Abdominal Compartment Society. Recent findings: The present article reviews the clinical conditions of ACS and IAH and the latest updates from pathophysiology to the new management flowchart resulting from the implantation of point-of-care ultrasound in the monitoring and assistance of medical treatment of IAH/ACS. Summary: The present review emphasizes the importance of IAH in daily clinical practice and brings new WSACS updates on monitoring and treatment.